Analisis Perubahan Fungsi Kawasan Hutan di Kabupaten Manokwari - Yohanes Yoseph Rahawarin; Hans Fence Zakeus Peday; Rudy Michael Yom; Jonni Marwa; Wolfram Yahya Mofu; Alexander Rumatora; Rusdy Angrianto; Christian Imburi (Bioscientist : Jurnal Ilmiah Biologi, 2022)
This study aims to analyze changes in the area and function of forest areas in Manokwari Regency from 1999 to 2014 using a Geographic Information System (GIS). This study uses a descriptive method with overlay techniques and maps analysis and secondary data, which consists of several stages including the preparation stage, the initial data processing, and processing stage, the ground checking stage, and the data analysis stage. The results showed that the change in the function of forest areas in Manokwari Regency based on the Decree of the Minister of Forestry Number: 891/Menhut-II/1999 to the Decree of the Minister of Forestry Number: 783/Menhut-II/2014, for a period of 15 (fifteen years), there has been a change in the function of the forest area which has an impact on reducing the area and changing the function of the forest area by 16,402,506 ha. This is mainly due to the release of forest areas from Convertible Production Forests (HPK) into Other Use Areas (APL) for development purposes. Factors that greatly influence the occurrence of changes in the area and function of forest areas are the release of forest areas in the context of plantation development, settlements, construction of office facilities and infrastructure, and construction of transportation support facilities.